Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Prerequisites - p.4 - Factoring Polynomials - Exercises - Page 39: 38



Work Step by Step

Use: $-3x=6x-9x$ $2x^2-3x-27=2x^2+6x-9x-27=2x(x+3)-9(x+3)=(2x-9)(x+3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.